A Study of Multiple Mappings in Multiplicative Metric Space - Gandhi, Manjusha P.; Aserkar, Anushree A.; Nafdey, Renuka (Communications in Mathematics and Applications, 2025)
A fixed point result for two pairs of maps has been established in multiplicative metric space. The continuous sub-compatible mappings satisfy the generalized contraction condition. This theorem improves the results, which are accessible in current literature. An example has been discussed in support of the present paper.
Keywords: Fixed point; Multiplicative Metric space; Continuously sub-compatible